SCIENCE LITERACY AND LEARNING OUTCOMES IN CELL MATERIAL: GUIDED INQUIRY IN CLASS XI SMA STUDENTS - Maharani, Rita Tri Maharani; Marinda Sari Sofiyana; Mar’atus Sholihah (Universitas Islam Balitar, 2024)
21st century learning requires students to have science literacy skills and learning outcomes. Learning that is still conventional and has not led to the empowerment of science literacy skills and learning outcomes results in students not being active in the learning process. This condition is reinforced by the fact that when the teacher poses problems, some students are still passive in expressing their ideas and arguments. One of the learning models that is considered to develop science literacy skills and learning outcomes is the guided inquiry learning model. This study aims to determine the effect of guided inquiry learning model on science literacy skills and learning outcomes of grade XI high school students. This type of research is a quasi experiment with Pretest-Posttest Control Group Design. Instruments used to measure science literacy and cognitive learning outcomes in the form of essay tests, while affective learning outcomes using questionnaires and psychomotor learning outcomes of students using observation sheets. Data analysis techniques for science literacy and cognitive learning outcomes used ANOVA test while affective and psychomotor learning outcomes used descriptive analysis. The results showed that the guided inquiry learning model had a positive and significant effect on science literacy and student learning outcomes in terms of cognitive, affective, and psychomotor aspects.